Xavier Andreu Miralles y Mónica Bolufer Peruga (eds.), «European Modernity and the Passionate South: Gender and Nation in Spain and Italy in the Long Nineteenth Century» - Amann, Elizabeth (Cuadernos de Ilustración y Romanticismo, 2024)
Reseña bibliográfica.